(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Stroke therapy has progressed through both conventional and novel methods, with a special emphasis on gait restoration. After a stroke, gait abnormalities are prevalent and can negatively affect mobility and quality of life. Though they are still useful, traditional physical therapy techniques like task-specific gait training are frequently constrained by patient-specific issues and resource availability. New technologies that improve the intensity, accuracy, and involvement of rehabilitation, such as neuromodulation, virtual reality, and robotics, present interesting options. However, there are obstacles to the clinical practice integration of these advanced medicines, including cost, accessibility, and the requirement for additional validation through long-term studies. It has been demonstrated that individualised therapy, catered to each patient’s deficits and objectives, improves adherence and results. Additionally, the utilisation of interactive and wearable technology supports patient motivation and involvement. Barriers including uneven progress measurement, inconsistent treatment outcomes, and unequal access to healthcare continue to exist despite these developments. Research to improve these treatments, comprehend the neuroplastic principles underpinning recovery, and address psychosocial aspects influencing rehabilitation success is becoming more and more necessary. The usage of cutting-edge technology will be improved, cost-effectiveness will be increased, and fair access to efficient treatments will be guaranteed. All things considered, increasing recovery and the quality of life for stroke survivors requires a multimodal, patient-centered approach to stroke rehabilitation that incorporates both established and cutting-edge therapies.